Las claúsulas penales espirituales en la documentación leonesa del siglo XII por un estudio de la sanctio - Martín López, María Encarnación (Estudios humanísticos. Geografía, historia y arte, 1990)
In this paper I consider documents formulae essential for the understanding of medieval religious thought. The clauses that contain that formulae while clearly reflecting the contemporanu religious mind, they have traditionally regarded as having a fixed and formulaic nature. However, as the latest studies on "diplomatics" show, quite the opposite is the truth. The aim of this paper is to make a contribution to the assessment of those clauses and specifically of the "sanctio".